Otoritas Ibn 'Asyur dalam Al-Tahrir Wa Al-Tanwir sebagai Pembentuk Wacana dalam Dunia Tafsir (Studi Pendekatan Michel Foucault) - Fathoni, Ahmad; Zakiy, Ahmad (Lembaga Yasin AlSys, 2024)
This study aims to explore aspects of Ibn 'Asyur's authority in the tafsir al-Tahrir wa al-Tanwir as a discourse shaper in the scientific world of Qur'anic interpretation. This type of research is library research with descriptive-analytical method. The approach to be used to achieve the research objectives is the archaeology of knowledge approach initiated by Michel Foucault in the concept of power and knowledge relations. The result of this research is that Ibn 'Asyur's tafsir al-Tahrir wa al-Tanwir has an important authority in the scientific world of tafsir. This is characterized by several things. First, the complexity of Ibn 'Asyur descriptions that contain various opinions of scholars without favoring one opinion with another opinion without rational reasons creates new developments in the science of interpretation. This creates its own authority because it is able to release the tendency of laziness by moving to the aspect of rationality. Second, his expertise in the field of maqashid al-syari'ah makes him able to understand the differences in each of the arguments of the scholars of different schools and sometimes seem contradictory. With such insight, Ibn 'Asyur was able to escape the subjetivity of the madhhab and chose to be objective by containing all opinions.